An Energy-Efficient and State-Aware Path Selection Technique in the Internet of Things - A. Thomas Felix and P. Calduwel Newton, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Recent developments in sensor and networking technologies have driven the growth ofInternet of Things (IoT) applications. In non-rechargeable environments, IoT devices aredecentralized systems with autonomous nodes that are limited in resources due to a lack of continuous connectivity or battery life.